2004
DOI: 10.1016/j.ydbio.2003.10.040
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Brahma (SWI/SNF) chromatin remodeling complex exhibits cell-type specific activation and repression functions

Abstract: The Brahma (Brm) complex of Drosophila melanogaster is a SWI/SNF-related chromatin remodeling complex required to correctly maintain proper states of gene expression through ATP-dependent effects on chromatin structure. The SWI/SNF complexes are comprised of 8-11 stable components, even though the SWI2/SNF2 (BRM, BRG1, hBRM) ATPase subunit alone is partially sufficient to carry out chromatin remodeling in vitro. The remaining subunits are required for stable complex assembly and/or proper promoter targeting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 78 publications
7
55
0
1
Order By: Relevance
“…Subsequently, whole-genome expression analysis in yeast demonstrated a role for the Swi͞Snf complex in transcriptional repression as well as activation. Intriguingly, studies examining wing vein development in Drosophila suggest that SNR1, the Snf5 Drosophila ortholog, may repress transcriptional activation by the ATPase Brm, a core Swi͞Snf subunit (22). We found that three times as many genes were activated (978) as repressed (322) after Snf5 inactivation in MEFs, suggesting that mammalian Snf5 may in fact act to repress transcriptional activation by the Swi͞Snf complex.…”
Section: Discussionmentioning
confidence: 59%
“…Subsequently, whole-genome expression analysis in yeast demonstrated a role for the Swi͞Snf complex in transcriptional repression as well as activation. Intriguingly, studies examining wing vein development in Drosophila suggest that SNR1, the Snf5 Drosophila ortholog, may repress transcriptional activation by the ATPase Brm, a core Swi͞Snf subunit (22). We found that three times as many genes were activated (978) as repressed (322) after Snf5 inactivation in MEFs, suggesting that mammalian Snf5 may in fact act to repress transcriptional activation by the Swi͞Snf complex.…”
Section: Discussionmentioning
confidence: 59%
“…Genetic Manipulations and Strains-Fly strains and manipulations used in this study have been previously described (15,16,39 (47), was controlled using the P(GawB)69B-GAL4 driver (48). Crosses were carried out at 18°C and appropriately staged pupae selected for RNA analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found that SNR1 functions to mediate aspects of Brm complex transcriptional repression in specific cells through shielding ATP-dependent gene activation, a mechanism that requires the coordinated activities of a tissue-specific transcription repressor and histone deacetylase activity (39). Taking advantage of conditional dominant-negative mutant alleles of snr1 and brm, we showed that cell-type or tissuespecific regulation of Brm complex activities may play an essential role in regulating key developmental growth and patterning processes (16,23,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although both major classes of chromatin remodeling complexes are likely to contribute to developmental processes, including those in the central nervous system (19 -21), evidence is emerging that the SWI/SNF chromatin remodeling complexes play an important role in the differentiation of specific cell types (22). For example, these complexes have been shown to facilitate the differentiation of a variety of cell types such as erythrocytes (7,23), macrophages (24), myeloid cells (25), adipocytes (26), myoblasts (27), osteoblasts (28), neurons (29,30), and glia (31).…”
mentioning
confidence: 99%